Grade 7 Learners’ Academic Achievement in Araling Panlipunan Using Contextualization of Teaching and Learning (CTL) - Ma.Bless Mignun N. Pepito; Kyle Aaron E. Moreno; Angelie D. Napala; Clent Argie Ampado; Lionel Frederich L. Tatoy; Jay C. Bansale (Scientia Publica Media, 2026)
This study aimed to assess the effectiveness of Contextualized Teaching and Learning (CTL) in enhancing the academic performance of thirty Grade 7 Mabolo students at Baybay National High School through CTL. Conducted during the first quarter of the Academic Year 2023-2024, the research utilized a pre- and post-intervention design incorporating CTL that lasted for 4 weeks. A mixed-method approach was employed to assess student performance, utilizing a contextualized lesson plan, checklist, 4-point Likert scale, a post-intervention assessment with 5 identification type, 5 multiple-choice, and 2 essay-type questions, including semi-structured interviews. The Cronbach Alpha of 0.714 was accepted after a pilot testing method. Data analysis involved the Wilcoxon signed-rank test and thematic analysis. Results revealed a significant improvement in student assessment scores, with the median score increasing from 4.000 (SD = 0.493) before the intervention to 4.667 (SD = 1.06) after the intervention. Interviews indicated that students perceived CTL as significantly enhancing their class participation and self-efficacy. Additionally, their familiarity with the topics improved through CTL, contributing to enhanced academic performance. The potential and effectiveness of CTL in Social Studies education have yielded promising outcomes. However, several areas require further development, including the consistency of implementation, teacher capacity, responsiveness to community contexts, and the availability of high-quality contextualized reference materials. School administrators can play a pivotal role by creating supportive spaces that enable Social Studies teachers to gather and utilize local data, thereby strengthening the integration of context into content. Furthermore, education policymakers can enhance CTL by establishing a more flexible and responsive contextualized matrix that accommodates diverse local realities and pedagogical approaches.